ANALISIS RESPON PENAWARAN, PERMINTAAN DAN HARGA UBI KAYU DI PROVINSI LAMPUNG - Prianando Tambunan, Varingan; Abbas Zakariya, Wan; Indriani, Yaktiworo (Journal of Food System & Agribusiness, 2023)
The purpose of this study was to analyze the factors that influenced the response of supply, demand and price of cassava in Lampung Province. The type of data used is secondary data with a time series for 15 years, from 2006 to 2019. The analytical method used is the Two-Stage Least Squares Analysis Method or TSLS with several equations used, namely cassava production or supply equation, cassava demand for cassava and tapioca industries, and farmer-level cassava prices in Lampung Province. The research found  factors that significantly influenced the cassava supply response in Lampung Province were the variables of harvested area and cassava productivity, the factors that significantly influenced the cassava demand response for the cassava industry were cassava price growth variables, loan interest rate variables, and the amount of cassava demand for the cassava industry in the previous year, while the factors that significantly influenced the cassava demand response for the tapioca industry were the variable tapioca price ratio at the tapioca industry level, factory labor wages, the price based on diesel fuel, technology, loan interest rates, and the amount of cassava demand at the tapioca industry level in the previous year, the factors that influence the response of cassava prices at the farmer level were the supply and demand for cassava.